In-situ remediation of hexavalent chromium contaminated groundwater and saturated soil using stabilized iron sulfide nanoparticles. (1st February 2019) - Wang, Tao; Liu, Yuanyuan; Wang, Jiajia; Wang, Xizhi; Liu, Bin; Wang, Yingxu
Abstract: Hexavalent chromium (Cr(VI)) is one of prevalent toxic and mobile heavy metal contaminants in the environment. In this study, synthetic iron sulfide nanoparticles (FeS NPs) stabilized with carboxymethyl cellulose (CMC) were applied to remediate Cr(VI) contaminated groundwater and saturated soil. The batch test results showed that aqueous Cr(VI) was removed with a capacity as high as 1046.1 mg Cr(VI) per gram of FeS NPs. The removal of aqueous Cr(VI) mainly involves adsorption, reduction and co-precipitation. Aqueous Cr(VI) removal by using FeS NPs was a strong pH-dependent process. Dissolved oxygen (DO) would compete with Cr(VI) for Fe(II) and S(-II) and inhibit the process of Cr(VI) reduction at pH 5.6. For ionic strength and natural organic matter (NOM), there were no significant influences on the aqueous Cr(VI) removal. Column tests demonstrated that the concentrations of Cr(VI) in the effluent were lower than 0.005 mg L −1 after an elution of 45 pore volumes (PVs) of stabilized FeS NPs suspension. The leached Cr(VI) decreased from 4.58 mg L −1 of raw Cr(VI)-contaminated soil to 46.8–80.7 μg L −1 from the surface to bottom treated soil in column through Toxicity Characteristic Leaching Procedure (TCLP). Therefore, the synthesized FeS NPs hold high potential for the in-situ remediation of Cr(VI)-contaminated groundwater and saturated soil. Graphical abstract: Image 1 Highlights: Synthetic FeS NPs effectively immobilized Cr(VI) in groundwater and saturated soil. Aqueous Cr(VI) removal by FeS NPs was significantly dependent on pH. FeS NPs removed aqueous Cr(VI) through adsorption, reduction and co-precipitation. In-situ remediation of Cr(VI) contaminated soil by FeS NPs soliquid was simulated.